8A.004 MV crash characteristics and medical charges: front-and rear-seated restrained and unrestrained adults. (14th March 2021) - Pressley, Joyce C; Bauer, Michael; Pawlowski, Emilia; Bhatta, Sabana; Hines, Leah
Abstract : Background: There are reports that historically higher mortality observed for front- compared to rear-seated adult motor vehicle (MV) occupants has narrowed. Vast improvements have been made in strengthening laws and restraint use in front-, but not rear-seated MV occupants suggesting there may be value in expanding the science on rear-seat safety. Methods: A linked 2016–2017 hospital and MV crash data set, the Crash Outcomes Data Evaluation System (CODES), was used to compare characteristics of front-seated (n=130, 761) and rear-seated (n=6, 641) adults aged 18 years and older involved in a MV crash in New York State (NYS). A primary enforced seatbelt law was in effect for front-seated, but not rear-seated occupants. Chi Square and linear regression use SAS 9.4. Results: Compared to front-seated occupants, those rear-seated were more likely to be unrestrained (21.2% vs. 4.3%, P<0.0001) and to have more moderate-to-severe injury/death (11.9% vs. 11.3%, p<0.0001). Compared to restrained rear-seated occupants, unrestrained rear-seated occupants had higher moderate-to-severe injury/death (21.5% vs. 7.5%, P<0.0001) and 4-fold higher hospitalization. Ninety percent (9 of 10) of rear-seated deaths were unrestrained. More than 95% of ejections were unrestrained and had 7-fold higher medical charges. Hospital stays were longer, hospital charges higher and societal financial costs higher as the unrestrained were more frequently uninsured/self-insured/government-insured. Conclusions: These findings document increased medical charges and support the need to educate consumers and policymakers on the risks associated with adults riding unrestrained in the rear-seat. Learning outcomes: Describe crash outcomes and medical charges in front- and rear-seated restrained and unrestrained adult passengers